Process Drama in the Japanese University EFL Classroom: The Emigration Project - Donnery, Eucharia (SCENARIO: Journal for Performative Teaching, Learning, Research, 2014)
This paper examines the impact of using a process drama project in a Japanese university EFL class focusing on the social issue of emigration from a historical perspective while simultaneously developing English communicative skills. Speaking in English is a skill that many Japanese people find challenging. There are a number of cultural reasons for this, for example the enormous linguistic gap between Japanese and English communicative patterns in terms of explicitness/implicitness, hierarchy, gender, and the role of silence. Therefore, the overt aim was to help students develop English language skills while learning about Japanese historical emigration through the medium of English with Japanese scaffolding. This is in keeping with the needs of the average Japanese university EFL student, who has had six years of accuracy-based study for the short-term target of the university entrance examination and who sees English in terms of mathematical code, rather than as a communicative tool. The narrative arc of the paper follows the Noh theatre JO-HA-KYU, Enticement- Elaboration-Consolidation trajectory to take the reader through the emigration process drama project held in the spring semester of 2009 at the School of Human Welfare Studies (HWS), Kwansei Gakuin University (KGU), Japan. The research approach was a mixed-method one and data was collected through digital recording of role-plays, student self-critical reflection by writing-in-role and writing out-of-role in an online class group, qualitative and quantitative questionnaires and teacher observation. Results indicated that process drama projects can have a positive influence on Japanese university EFL learners from the perspective of both linguistic and intercultural communicative competence.